The No-Nonsense Guide to Tourism - Tufts, Steven (Labour / Le Travail, 2008)
The article reviews the book, "No-Nonsense Guide to Tourism," by Pamela Nowicka.
Keywords: BOOKS -- Reviews; NO-Nonsense Guide to Terrorism, The (Book); NOWICKA, Pamela; Nonfiction; Tourism